Pelatihan Manajemen Berbasis Teknologi Digital pada BUMG Ujong Baroh Kabupaten Aceh Barat - Alisman Alisman; Zainal Putra; Puput Arisna; M. Rahmat Hidayat; Rusdi Rusdi; Hartini Hartini; Yenni Ertika; Dedi Sufriadi (Indo Publishing, 2025)
The purpose of this community service activity is to create a strong BUMDes in Gampoeng Ujong Baroh, Johan Pahlawan District, West Aceh Regency, both in terms of Innovation, institutions and financial management based on transparency and accountability. This community service was carried out in Gampoeng Ujong Baroh, Johan Pahlawan District, West Aceh Regency in June 2025. Management training was carried out in two sessions. The first training session was carried out by the community service with the material